Increased Macrophages and C1qA, C3, C4 Transcripts in the Midbrain of People With Schizophrenia - Purves-Tyson, Tertia D.; Robinson, Kate; Brown, Amelia M.; Boerrigter, Danny; Cai, Helen Q.; Weissleder, Christin; Owens, Samantha J.; Rothmond, Debora A.; Shannon Weickert, Cynthia (Frontiers in Immunology, 2020)
Increased cytokine and inflammatory-related transcripts are found in the ventral midbrain, a dopamine neuron rich region associated with schizophrenia symptoms. In fact, half of schizophrenia cases can be defined as having a “high inflammatory/immune biotype”. Recent studies implicate both complement and macrophages in cortical neuroinflammation in schizophrenia. Our aim was to determine whether measures of transcripts related to phagocytosis/macrophages (CD163, CD64, FN1), or related to macrophage adhesion [intercellular cell adhesion molecule 1 (ICAM1)], or whether CD163+ cell density, as well as protein and/or gene expression of complement pathway activators (C1qA) and mediators (C3 or C4), are increased in the midbrain in schizophrenia, especially in those with a high inflammatory biotype. We investigated whether complement mRNA levels correlate with macrophage and/or microglia and/or astrocyte markers. We found CD163+ cells around blood vessels and in the parenchyma and increases in ICAM1, CD163, CD64 and FN1 mRNAs as well as increases in all complement transcripts in the midbrain of schizophrenia cases with high inflammation. While we found positive correlations between complement transcripts (C1q and C3) and microglia or astrocyte markers across diagnostic and inflammatory subgroups, the only unique strong positive correlation was between CD163 and C1qA mRNAs in schizophrenia cases with high inflammation. Our study is the first to suggest that more circulating macrophages may be attracted to the midbrain in schizophrenia and increased macrophages are linked to increased complement pathway activation in tissue and may contribute to dopamine dysregulation in schizophrenia. Single cell transcriptomic studies and mechanistic preclinical studies are required to test these possibilities.